Bellas Artes histórico : conjeturas y controversias sobre el proceso fundacional de la Escuela de Bellas Artes de Manizales - Matijasevic, Vicente, 1957- (Colección Artes y humanidades., 2014)
History and foundation data on the School of Fine Arts of the city of Manizales (Department of Caldas in Central Colombia), the first art school of the city that later (in 1957) became the Department of Fine Art of the University of Caldas.